2012
DOI: 10.1017/s0307472200017442
|View full text |Cite
|
Sign up to set email alerts
|

Creative Commons licences: are they right for you?

Abstract: This article provides an introduction to the use of the Creative Commons licence system, and sets it in a historical, economic and political context. It is written from the perspective of involvement in open educational projects in an arts university that has used the licences. A description of the fundamental features of the licences and their uses is given, together with an outline of how the Creative Commons organisation works and its strategic aims. An assessment of the usefulness of these licences is prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…KreljaKurelovic (2016) found that "the familiarity with OER and Creative Commons licenses [among the participants in Croatia] is very low". Another study revealed a low level of awareness of the CC licenses among UK art and design academics(Casey, 2012). Similarly,Marín et al (2022) highlighted the lack of awareness level and adoption practice among faculty members, and the availability of institutional repositories as a barrier in nine countries including Australia and Germany.…”
mentioning
confidence: 99%
“…KreljaKurelovic (2016) found that "the familiarity with OER and Creative Commons licenses [among the participants in Croatia] is very low". Another study revealed a low level of awareness of the CC licenses among UK art and design academics(Casey, 2012). Similarly,Marín et al (2022) highlighted the lack of awareness level and adoption practice among faculty members, and the availability of institutional repositories as a barrier in nine countries including Australia and Germany.…”
mentioning
confidence: 99%